Domestic Violence In Muslim Societies: A Legal Sociology Perspective - Haji Harun, Makmur; Hosaini (EDUCATE : Journal of Education and Culture, 2025)
Domestic violence or violence within the household (KDRT) remains a prevalent social phenomenon in society, including within Muslim communities. This study aims to analyze domestic violence through the lens of the sociology of law, focusing on how social norms, cultural values, and Islamic teachings influence the understanding and enforcement of laws related to domestic violence. From a sociological legal perspective, law is not merely seen as a set of formal rules, but also as a reflection of the values and social structures prevailing in society. This research employs a qualitative method with a literature review approach, examining Islamic legal literature, scholarly opinions, and the social realities underlying the practice of domestic violence. The analysis reveals that although Islam explicitly teaches compassion and justice within the family, misinterpretations of religious texts and patriarchal cultural norms are often used to justify acts of violence. Therefore, a legal approach that is not only normative but also responsive to social realities is needed to prevent and address domestic violence within Muslim communities.